Risk factors for hypotony after transconjunctival sutureless vitrectomy - Takumi Ando; Hiroko Terashima; Kazuma Fujii; Hiromitsu Yoshida; Eriko Ueda; Yohei Nozaki; Naoya Shiozaki; Kiyoshi Yaoeda; Takeo Fukuchi (PLoS ONE, 2025)
Purpose To identify risk factors for unexpected hypotony after transconjunctival sutureless vitrectomy (TSV). Methods In this retrospective observational study, we defined postoperative hypotony as intraocular pressure (IOP) < 6 mmHg on the day after TSV and performed multivariate analysis after dividing patients into hypotony and non-hypotony groups. Peripheral vitrectomy with scleral compression was performed for all patients and completed with normal IOP and no sutures. Results Eight-hundred and forty eyes of 748 consecutive patients who underwent 25-G or 27-G TSV were included. Postoperative hypotony occurred in 139 eyes (16.5%) and was associated with longer axial length (AL) (odds ratio [OR], 0.86; P = 0.001) and no tamponade usage (OR, 0.50; P = 0.001). Postoperative complications occurred more frequently in the hypotony group than in the non-hypotony group (51.1% vs. 11.3%, P < 0.001), especially choroidal fold (47.5%) and hypotony maculopathy (2.2%). On dividing patients without tamponade into 3 AL-based groups, the ≥26-mm group had significantly higher hypotony incidence than the 23–26-mm group (33.3% vs. 18.4%; P = 0.024). Conclusion Longer AL and no tamponade usage influenced hypotony post-TSV. In patients with these factors, especially with AL ≥ 26 mm, surgeons may aggressively consider suturing sclerotomy to minimize hypotony-related complications.